Penyelesaian Sengketa Komisi Informasi Kota Cirebon Berdasarkan Undang-Undang Nomor 14 Tahun 2008 Tentang Keterbukaan Informasi Publik - Sultan Pramudita; Wing Redy Prayuda (PEPAKEM: JURNAL HUKUM TATA NEGARA DAN POLITIK ISLAM, 2025)
The constitutional right to information requires not only open public bodies but also an accessible and effective remedy when information requests are rejected or ignored. This study analyzes the legal mechanism and institutional effectiveness of public information dispute resolution at the Cirebon City Information Commission under Law Number 14 of 2008. It employs empirical legal research with statutory, conceptual, and institutional approaches. Primary data derive from institutional observation and field-practice information concerning information services, mediation, non-litigation adjudication, monitoring, and administrative support. Secondary legal materials include legislation, Information Commission regulations, official guidelines, and scholarly literature. The data are qualitatively analyzed using five indicators: accessibility, timeliness, procedural certainty, party compliance, and the practical effectiveness of decisions. The findings show that dispute resolution follows a structured sequence consisting of an information request, administrative objection, registration, preliminary examination, mediation, and non-litigation adjudication. The mechanism offers a simpler and more affordable forum than ordinary litigation. Nevertheless, its effectiveness is constrained by limited procedural literacy, uneven capacity of information officers, weak records management, non-attendance or lack of authority among public-body representatives, limited institutional resources, and dependence on courts when decisions are not voluntarily implemented. The study argues that effective dispute resolution requires preventive information services, strict and limited interpretation of exemptions, professional mediation, reasoned adjudication, digital administration, transparent publication of decisions, and systematic compliance monitoring.